A Computer-Based Air-Fuel Model for Analysing the Performance of Spark-Ignition Internal Combustion Engines (University of Khartoum Engineering Journal, 2022)
This paper presents a computer-based thermodynamic model of spark-ignition (SI) internal combustionm engines. The air-fuel formulation enables the model to analyse the engine's performance with conventional and alternative fuels. The paper describes the mathematical formulation of the model and outlines the main features of its computer code. The model was verified against published results of earlier fuel-inducted air-fuel models andthen used to analyse the performance of a SI engine with ethanol and ethanol-gasoline mixture. The engine's efficiency and indicated mean effective pressure were evaluated at different engine speeds, compression ratios and equivalence ratios.